Cu(ii) phenanthroline–phenazine complexes dysregulate mitochondrial function and stimulate apoptosis. Issue 1 (13th November 2019) - Rochford, Garret; Molphy, Zara; Kavanagh, Kevin; McCann, Malachy; Devereux, Michael; Kellett, Andrew; Howe, Orla
Abstract : Herein we report the central role of the mitochondria in the cytotoxicity of four developmental cytotoxic copper(ii ) complexes [Cu(phen)2 ] 2+, [Cu(DPQ)(Phen)] 2+, [Cu(DPPZ)(Phen)] 2+ and [Cu(DPPN)(Phen)] 2+ superior to cisplatin and independent of resistance in a range of cells. Abstract : Herein we report an in-depth study on the cytotoxic mechanism of action of four developmental cytotoxic copper(ii ) complexes: [Cu(phen)2 ] 2+ (Cu-Phen); [Cu(DPQ)(Phen)] 2+ (Cu-DPQ-Phen); [Cu(DPPZ)(Phen)] 2+ ; and [Cu(DPPN)(Phen)] 2+ (where Phen = 1, 10-phenanthroline, DPQ = dipyrido[3, 2- f :2′, 3′- h ]quinoxaline, DPPZ = dipyrido[3, 2- a :2′, 3′- c ]phenazine, and DPPN = benzo[ i ]dipyrido[3, 2- a :2′, 3′- c ]phenazine). This complex class is known for its DNA intercalative properties and recent evidence—derived from an in vivo proteomic study—supports the potential targeting of mitochondrial function. Therefore, we focused on mitochondrial-mediated apoptosis related to cytotoxic activity and the potential impact these agents have on mitochondrial function. The Cu(ii ) complexes demonstrated superior activity regardless of aromatic extension within the phenazine ligand to the previously demonstrated activity of cisplatin. Unique toxicity mechanisms were also identified in prior demonstrated cisplatin sensitive and resistant cell lines. Double strand breaks in genomic DNA, quantified by γH2AX foci formation, were then coupled with apoptotic gene expression to elucidate the mechanisms of cell death. These results indicate that while DNA damage-induced apoptosis by BAX, XIAP and caspase-9 and -3 expression is moderate for the Cu(ii ) complexes when compared to cisplatin, protein targets independent of DNA exert a multimodal mechanistic effect. Significantly, mitochondrial gene expression of oxidative stress, protease expression, and fission/fusion processes—upregulated HMOX, DRP1 and LON, respectively—indicated an increased oxidative damage associated with compromised mitochondrial health upon exposure to these agents. These data support a unique mode of action by these complexes and provide valuable evidence of the developmental potential of these therapeutic inorganic complexes.